A tetrachlorinated molecular non-fullerene acceptor for high performance near-IR absorbing organic solar cells. Issue 34 (22nd August 2018) - Laventure, Audrey; Welch, Gregory C.
Abstract : Installation of chlorine atoms into the ITIC non-fullerene acceptor enables low energy photon harvesting generating high photocurrent in OSCs when paired with PBDB-T. The active layer morphology is greatly influenced by solvent additives. Abstract : We detail the physical properties and organic photovoltaic (OPV) performance of a tetrachlorinated fused ring non-fullerene acceptor. Introduction of chlorine atoms red-shifts the optical absorption out to 850 nm leading to low energy photocurrent generation in solar cell devices using the donor polymer PBDB-T. Processing films with different volatile solvent additives affects the active layer morphology and open-circuit voltage ( V oc ). The best solar cells exhibit power conversion efficiencies over 9%.